2006
DOI: 10.1073/pnas.0602828103
|View full text |Cite
|
Sign up to set email alerts
|

On the hand-over-hand mechanism of kinesin

Abstract: We present here a simple theoretical model for conventional kinesin. The model reproduces the hand-over-hand mechanism for kinesin walking to the plus end of a microtubule. A large hindering force induces kinesin to walk slowly to the minus end, again by a hand-over-hand mechanism. Good agreement is obtained between the calculated and experimental results on the external force dependence of the walking speed, the forward͞backward step ratio, and dwell times for both forward and backward steps. The model predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 37 publications
2
46
0
Order By: Relevance
“…Joining a specific nanometry technique with fluorescence microscopy, they showed that the myosin head can make several steps along the actin filament per ATP molecule hydrolyzed [21,22]. This observation was confirmed in some other laboratories for myosin [23], dynein [24,25] and kinesin [26]. In Fig.…”
Section: The Problem Of Molecular Gearsupporting
confidence: 54%
“…Joining a specific nanometry technique with fluorescence microscopy, they showed that the myosin head can make several steps along the actin filament per ATP molecule hydrolyzed [21,22]. This observation was confirmed in some other laboratories for myosin [23], dynein [24,25] and kinesin [26]. In Fig.…”
Section: The Problem Of Molecular Gearsupporting
confidence: 54%
“…Previous measurements of the mechanical properties of two‐headed kinesin indicated that the kinesin stall force might be determined by (1) the binding affinity of the head to the microtubule in the strongly bound state and (2) the ATP‐binding kinetics to the nucleotide‐free head (Visscher et al , 1999; Nishiyama et al , 2002; Lakämper and Meyhöfer, 2005; Shao and Gao, 2006). Thus, the kinesin stall force exerted on the mutated microtubules with reduced affinity for kinesin in AMP‐PNP state is expected to be smaller than that exerted on the wild‐type microtubules.…”
Section: Resultsmentioning
confidence: 99%
“…Although the structural elements that determine the shape of the binding potential for strong binding have not been fully identified, the measurement of the stall force demonstrated that the size of the stall force was linearly related to the unbinding force for minus‐end loading, but it was independent of the unbinding force for plus‐end loading (Figure 5C). As predicted from the analyses of the force‐velocity relationship of single kinesin molecule (Visscher et al , 1999; Nishiyama et al , 2002; Carter and Cross, 2005; Lakämper and Meyhöfer, 2005; Shao and Gao, 2006), for two‐headed kinesin to produce force, it might be crucial for the trailing head in the strong binding state to sustain against the load imposed towards the minus‐end direction. Our result is the first direct demonstration that the stall force is directly related to the stability of the strong binding state.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent singlemolecule (SM) experiments have shown that, with each stepping motion being strongly coupled to the ATP, the kinesin moves toward the (ϩ) ends of MTs by taking discrete 8-nm steps (3-7) in a hand-over-hand fashion (4,7,8). Although the ultimate understanding of kinesin's motility is still far from completion, the SM experiments (3)(4)(5)(6)(7)(8)(9), together with the series of kinetic ensemble measurements (10)(11)(12)(13) and theoretical studies (14)(15)(16)(17)(18)(19), begin providing glimpses to the physical principle of how kinesin walks.…”
Section: F Irst Recognized By Means Of Their Close Relationship Betweenmentioning
confidence: 99%